CHARCOAL OBTAINED BY PHYSICAL ACTIVATION OF MAMEY (MAMEY) SEED AND ITS USE AS AN ADSORBENT OF COPPER (II) IONS - Prieto García, Julio Omar; Pérez Leiva, Ariel; Curbelo Sánchez, Alfredo E.; Enríquez García, Mixary; Mollineda Trujillo, Ángel (Centro Azúcar Journal, 2025)
Introduction: Charcoals obtained by chemical and physical activation are good adsorbents of gases, molecules and ions in aqueous solution. Objective: To obtain the mathematical parameters of the kinetic, thermodynamic and diffusive processes of the heterogeneous system in equilibrium aqueous solution of copper (II)- charcoal. Materials and Methods: Copper (II) solutions are used. Charcoal is synthesized by physical activation of mamey seeds and its chemical and physical parameters are determined. The kinetic and diffusive equations at 298 and 338 K are used. The adsorption isotherm is determined at 298 K. Results and Discussion: With a 47.6% yield, a coal with a high tortuosity and C/N ratio is obtained. The activation energy of 8.18 kJ/mol. The Temkin isotherm fits the thermodynamic data. Conclusions: 1. Charcoal is a good adsorbent of Cu(II) ions. 2. The kinetic equations respond to a pseudo-first order. 3. Diffusion coefficients of the order of 10-10 m2/s are obtained.